Effects of chemical modifications on hemoglobin’s toxicity towards human cardiac myocytes - Jana, Sirsendu; Garbus-Grant, Haley; Kassa, Tigist; Alayash, Abdu I. (Frontiers in Molecular Biosciences, 2025)
BackgroundHemoglobin-based oxygen carriers (HBOCs) also known as blood substitutes were developed by chemical or genetic alterations of cell-free human or bovine Hbs to prolong the circulation time of Hb and to improve its ability to unload oxygen. However, toxicity and safety issues led to the termination of several clinical trials. The most persistent observation was the development of cardiac lesions after transfusion of some HBOCs in animal models. Oxidation of HBOCs in circulation, subsequent heme release and cellular uptake are thought to play an important role in the overall toxicity of HBOCs.MethodsWe examined the effects of different redox states, ferrous (Fe+2), ferric (Fe+3) and ferryl (Fe+4) of four different HBOCs on cardiomyocyte integrity and mitochondrial respiration. The HBOC formulations used in this study were two-human derived and two bovine-derived molecules. We analyzed cellular and subcellular impacts of these forms including mitochondrial electron transport chain (ETC.) complexes individually by measuring the enzymatic activities of Complex I, Complex II-III, and Complex IV.ResultsThe ferrous, and ferric forms of these HBOCs generally induced minimum lactate dehydrogenase (LDH) release from human cardiac myocytes (AC16). Meanwhile higher oxidation state, ferryl forms of all HBOCs generated substantial cell injury as measured by LDH levels. We examined the effects of these redox forms of HBOCs and their ability to impair bioenergetic function of cultured AC16 cells. The ferrous forms of HBOCs did not cause measurable impairment of mitochondrial ETC functions, whereas ferric non-functional versions of all the HBOCs caused a significant loss of Complex IV activity but not Complex I or II-III in those cardiac cell lines. On the other hand, complex I, II-III and IV activities were completely blunted by the ferryl forms of HBOCs.ConclusionThis study for the first time investigated the impact of different chemical modifications on the redox activities of HBOCs towards mitochondrial complexes in cardiac myocytes. Higher oxidation ferryl states once formed trigger cellular and subcellular changes in cardiac myocytes. Our findings on the impact of HBOC redox states on mitochondrial function may therefore inform future design of alternative molecular entities to ensure safety and minimize toxicity.